ANALISIS USAHATANI CABE MERAH (Capsicum Annum L) DI DESA PEREAN TENGAH, KECAMATAN BATURITI, KABUPATEN TABANAN - AGUNG, I DEWA GEDE; PUTU ARTINI, NI WAYAN; RATNA DEWI, NYOMAN (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
This research was carried out to study farmer’s income and profit gain from farm ordinary chili. The research is conducted at Perean Tengah village, Baturiti district, Tanbanan regency. Thirty farmers who done ordinary chili with monoculture system was taken randomly as samples. The result of the research show the average large farmbusiness was 0.14 hectar with 1,670 kg products each farm (11,929 kg/hectar). While average revenne was Rp 13,999,610.00 each farm (Rp 99,997,214.00/hectar) with the chili price Rp 8,383.00/kg. Meanwhile farmer expenditure for each farm was Rp 2,296,350.00 (Rp 16,402,500.00/hectar), so farmer’s income and net profit were Rp 12,141,229.00 and Rp 11,703,260.00 each farm respectively with Return-Cost-Ratio was 6.10, its mean that the chili farmbusiness give much benefit to the farmers.
Keywords: Farmbusiness, Revenne, Profit, Return-Cost-Ratio.